When Faster Is Slower. - Armour, Phillip G. (Communications of the ACM, 2013)
The article considers the merits of integrated development environments (IDEs) in computer software development. A brief history of software development and computer programming is also provided. According to the author, IDEs enable the development and testing of complex systems in a matter of days or hours. He explains the difference between experimenting and thinking in relation to systems development, as well as the effect of faster development tools on the cost of programming tasks. The goal of systems development is also discussed.